Introduction - Ng-A-Fook, Nicholas (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
It is an exciting time, and also a difficult time, to live and work as educational researchers. Canada remains a vast territory constituted by provincial, territorial, and Indigenous sovereign borders. Come this July, some of us will celebrate the constitutional establishment of our settler nation-state. We will reflect on the contributions our research has (or has not) made to the lives of various educational stakeholders. Whereas, other First Nations, Inuit, and Métis communities are still calling for constitutional recognition of their sovereignty both inside and outside of our settler academies. Such tensions of present absence have, and continue to exist, within this special capsule celebrating the 40th anniversary of the Canadian Journal of Education.